Short-Term Effectiveness, Safety, and Potential Predictors of Response of Secukinumab in Patients with Severe Hidradenitis Suppurativa Refractory to Biologic Therapy: A Multicenter Observational Retrospective Study - Pablo Fernandez-Crehuet; Sofía Haselgruber; Alicia Padial-Gomez; Fiorella Vasquez-Chinchay; Maria Dolores Fernandez-Ballesteros; Irene López-Riquelme; David Jimenez-Gallo; Juan Manuel Segura-Palacios; Marisol Contreras-Steyls; Giovana Fernanda Osorio-Gómez; Juan Carlos Hernández-Rodríguez; Manuel Sanchez-Diaz; et al. (Adis, Springer Healthcare, 2023)
Abstract Introduction Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease. Biologic drugs have a key role in the long-term anti-inflammatory treatment of moderate to severe patients due to their immunomodulatory properties. The aim of this study is to evaluate the effectiveness and safety of secukinumab in patients with moderate to severe HS after 16 weeks of treatment, and to explore potential predictors of clinical response to the drug. Methods Multicenter observational retrospective study. Patients treated with secukinumab 300 mg every 2 or 4 weeks who had completed at least 16 weeks of follow-up from nine hospitals based in southern Spain (Andalusia) were included in this study. Treatment effectiveness was assessed using the Hidradenitis Suppurativa Clinical Response (HiSCR). Information about adverse events was collected, the therapeutic burden of the patients was calculated as the summation of systemic medical treatments and surgical interventions (excluding incision and drainage) experienced until the start of secukinumab treatment. Results Forty-seven patients with severe HS were included for analysis. At week 16, 48.9% (23/47) of patients achieved HiSCR. Adverse events were present in 6.4% (3/47) of the patients. The multivariate analysis showed that female sex and, to a lesser extent, lower body mass index (BMI) and a lower therapeutic burden were potentially associated with a higher probability of HiSCR achievement. Conclusions Favorable short-term effectiveness and safety of secukinumab in the treatment of severe HS patients were observed. Female sex, lower BMI and a lower therapeutic burden may be associated with a higher probability of achieving HiSCR.